STRATEGI PENGELOLAAN KELAS INKLUSIF DALAM MENINGKATKAN KETERCAPAIAN PROGRAM PEMBELAJARAN INDIVIDUAL PESERTA DIDIK BERKEBUTUHAN KHUSUS - Amin, M; Yuni Alfiyah, Hanik; Azizah , Nur (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This study aims to describe how the effectiveness of inclusive classroom management in improving individual program achievement of students with special needs at MI Badrussalam Surabaya. This study used descriptive qualitative method. Based on the results of the data obtained in the field through interviews, observation and documentation that the learning carried out at MI Badrussalam Surabaya adapts students with special needs (PDBK), each child has a learning program design tailored to their learning needs. If the management of learning in classrooms where PDBK children respond to their learning needs the results will be more optimal and this requires the cooperation of all parties, starting from the special supervising teacher who handles PDBK with the class teacher who teaches in class every day. Including classroom teacher learning plans adapted to the individual PDBK program.